Lack of association of vitamin D receptor BsmI gene polymorphism with bone mineral density in Spanish postmenopausal women - Moran,Jose M.; Pedrera-Canal,Maria; Rodriguez-Velasco,Francisco J.; Vera,Vicente; Lavado-Garcia,Jesus M.; Fernandez,Pilar; Pedrera-Zamorano,Juan D. (PeerJ, 2015)
Osteoporosis is a polygenic disorder that is determined by the effects of several genes, each with relatively modest effects on bone mass. The aim of this study was to determine whether the vitamin D receptor single nucleotide polymorphism BsmI is associated with bone mineral density (BMD) in Spanish postmenopausal women. A total of 210 unrelated healthy postmenopausal women aged 60 ± 8 years were genotyped using TaqMan® SNP Genotyping Assays. Lumbar and femoral BMD were determined by dual-energy X-ray absorptiometry (DEXA). Daily calcium and vitamin D intake were determined by a food questionnaire. No differences were found in the femoral neck, trochanter, Ward’s Triangle, L2, L3, L4, L2-L4, or between the femoral neck and total hip BMD after further adjustment for potential confounding factors (P > 0.05) (age, BMI, years since menopause and daily calcium intake). The BsmI polymorphism in the VDR gene was not associated with BMD in Spanish postmenopausal women.
Keywords: VDR polymorphism; BsmI; Postmenopausal; Osteoporosis